Comparison of ITO and ZnO ternary glassy composites in terms of radiation shielding properties by Monte Carlo N-particle transport code and BXCOM - Toker, Ozan; Bilmez, Bayram; Kavanoz, H. Birtan; Akcali, Ozgur; Icelli, Orhan (SPRINGER, 2020)
In the present study, radiation shielding properties of two glassy composite materials that are widely used in electronics, photovoltaic applications, and sensor technology, were investigated in the photon energy range from 15 keV to 15 MeV. The materials chosen were (ITO)/V2O5/B2O3 and ZnO/V2O5/B2O3 including various concentrations of B2O3. Radiation interaction was simulated and shielding parameters calculated by means of the MCNP and BXCOM codes. More specifically, buildup factors, effective electron density (N-eff) and effective atomic number (Z(eff)) were calculated with BXCOM, while mass attenuation coefficients (mu/rho), half-value layer (HVL) and tenth-value layer (TVL) values were calculated with MCNP. The results were compared with those obtained with the WinXCOM code, for validation. Acceptable and preferable results were obtained for both composites as alternative to other glassy shielding materials. The composite including ITO showed better shielding properties than the composite including ZnO. In terms of radiation shielding, both composites turned out to be better than concrete and close to lead.
Keywords: ITO; ZnO; Effective atomic number; Buildup factor; MCNP 6.2; GAMMA-RAY; TELLURITE GLASSES; VANADIUM SLAG; ATTENUATION; OXIDE; PHOTOLUMINESCENCE; COMPUTATION; PHOTON; Life Sciences & Biomedicine - Other Topics; Biophysics; Environmental Sciences & Ecology; Radiology, Nuclear Medicine & Medical Imaging